Analisis Pengaruh Sumber Daya Manusia, Pemanfaatan Teknologi Informasi dan Pengendalian Internal Terhadap Ketepatwaktuan Pelaporan Keuangan Desa (Studi Kasus Pada Pemerintah Desa di Wilayah Kecamatan Kembang, Bangsri Mlonggo Kabupaten Jepara) - Yanto Yanto; Burhanuddin Burhanuddin (Jurnal Rekognisi Akuntansi, 2018)
This study aims to examine the Effect of Human Resources, Utilization of Information Technology, Internal Control on Timeliness of Village Financial Reporting. This type of research is classified as descriptive analysis research. Respondents in this study were village heads/high-ranking officials in the Kembang sub-district, Bangsri, Mlonggo, Jepara Regency, totaling 30 people. The sampling technique used is the survey method. The method of data collection is by distributing questionnaires. Data analysis technique using multiple regression with t test. The results of the test obtained are that the Human Resources and Information Technology Utilization variables have no significant effect on the Timeliness of Village Financial Reporting, while the Internal Control variable has a significant effect on the Timeliness of Village Financial Reporting.